Participation of ascorbic acid in the dormancy establishment of poplar lateral branch buds - Gergoff Grozeff, Gustavo Esteban (2014)
This work studied the participation of ascorbic acid (AA) in the dormancy establishment of apical buds of poplar (Populus deltoides Bartram ex Marshall cv. Catfish 2) lateral branches. AA content was highest during the active growth period and decreased to the lowest content during bud dormancy. The accumulation of the oxidised form, dehydroascorbate, was similar in either growth or dormant bud stages. The supplementation of buds with AA at the end of the summer delayed bud set. Similarly, the supplementation of buds with gibberellic acid extended the growth period and kept a high AA content in the apoplast. These results suggest that a decrease in the accumulation of reduced AA might be needed for the dormancy establishment in apical buds of poplar lateral branches.